PENILAIAN KINERJA KEUANGAN KOPERASI SIMPAN PINJAM CREDIT UNION (CU) SINAR HARAPAN JAWA TIMUR BERDASARKAN ANALISIS RASIO LIKUIDITAS DAN RASIO SOLVABILITAS SERTA RASIO PROFITABILITAS - Yulaekah, Maria Siti; Nurdiwaty, Diah; Tohari, Amin (Universitas Nusantara PGRI Kediri, 2023)
Financial performance in a cooperative can be identified by identifying various items in a financial report. This study aims to assess the financial performance of the Sinar Harapan East Java credit union saving and loan cooperative for the period 2019 – 2021. Using liquidity ratios (current ratio), solvency (debt to total asset ratio) and profitability (net profit margin). Data collection is done by documentation and interviews. The documentation here is secondary data in the form of income statements and balance sheets obtained from KSP CU Sinar Harapan, East Java. The type of research used is quantitative with ex post facto methods. The analysis used is multiple linear regression analysis with SPSS software. The conclusions of the results of this study are (1) Liquidity Ratio (CR) has a partial effect on financial performance at KSP CU Sinar Harapan. (2) The Solvency Ratio (DAR) has a partial effect on the financial performance of KSP CU Sinar Harapan. (3) Profitability ratios (NPM) have a partial effect on financial performance at KSP CU Sinar Harapan. (4) Liquidity Ratio (CR), Solvability Ratio (DAR), Profitability Ratio (NPM) simultaneously affect the financial performance of KSP CU Sinar Harapan.